The diagnostic survey method in socio-logopaedics - Wolańska, Ewa; Wolański, Adam (Papers in Linguistics, 2025)
The diagnostic survey method is a way of collecting information about opinions, views, feelings, and awareness of selected groups (respondents). It allows the researcher to examine phenomena that are somewhat dispersed in the entire society and do not have an institutionalized location. It provides information about the intensification or weakening of particular phenomena. This method is well suited for research conducted within the framework of socio-logopaedics, a subdiscipline of speech and language therapy that deals with, among other matters, the study of the speech awareness of patients undergoing therapy, their caregivers, as well as speech therapists or professionals collaborating with them. The results of such research can be useful, e.g. when developing various speech therapy preventive programmes or creating new programmes for training speech therapists or specialists working with them. This method can also be successfully used in sociolinguistic, pragmalinguistic, and language didactics research.